A New Drainpipe‐Envelope Concept for Subsurface Drainage Systems in Irrigated Agriculture†. (9th May 2018) - Bahçeci, Idris; Nacar, Abdullah Suat; Topalhasan, Lui; Tari, Ali Fuat; Ritzema, Henk P.
Abstract: On irrigated lands, drainpipe performance is often below standard due to clogging, siltation and root growth inside the pipe. To tackle these problems, an innovative pipe–envelope concept was tested on a 50 ha pilot area in Harran, Turkey, in 2015 and 2016. The new concept, HYDROLUIS, consists of a corrugated inner pipe with three rows of perforations at the top and an unperforated outer pipe that covers about 2/3 of the inner pipe leaving only the unperforated bottom part of the inner pipe in contact with the soil. The main advantages of the new concept are that it works for a wide range of soil textures and there is better protection against root growth inside the pipe. The new concept was compared with a geotextile envelope, a gravel envelope and a control with no envelope. The HYDROLUIS and gravel envelopes had a significantly lower entrance resistance compared to the geotextile, the best drain performance and no signs of sedimentation nor of root growth inside the pipe. The production costs of the HYDROLUIS envelope are comparable to those of pre‐wrapped synthetic envelopes and considerably lower than gravel envelopes. It can be concluded that the HYDROLUIS envelope is a promising alternative for sand/gravel or synthetic envelopes in irrigated lands. © 2018 The Authors. Irrigation and Drainage published by John Wiley & Sons Ltd on behalf of International Commission for Irrigation and Drainage